2011
DOI: 10.1366/10-05974
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crude Oil Products Using Data Fusion of Process Raman, Infrared, and Nuclear Magnetic Resonance (NMR) Spectra

Abstract: Process Raman, infrared (IR), and nuclear magnetic resonance (NMR) analyses are currently being performed in industrial settings for the monitoring of large scale reactions. These methods offer a distinct set of advantages such as no sample preparation and rapid noninvasive remote analysis. Process Raman spectroscopy offers information pertaining to the molecular backbone as well as symmetrical non-polar groups. IR spectroscopy yields information pertaining to hydrogen bonding and asymmetric polar groups. NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Several studies described data fusion techniques combining chemical data of different analytical methods (Dearing, Thompson, Rechsteiner, & Marquardt, 2011;Mas, Tauler, & de Juan, 2011;Pere-Trepat & Tauler, 2006;Smilde, van der Werf, Bijlsma, van der Werff-van der Vat, & Jellema, 2005;Vera et al, 2011;Xu, Correa, & Goodacre, 2013). Most of them applied fused chromatographic techniques with a complementary analytical tool (Forshed, Idborg, & Jacobsson, 2007;Mas et al, 2011;Pere-Trepat & Tauler, 2006;Vera et al, 2011).…”
Section: Chemometric Analysis Of Combined Datamentioning
confidence: 99%
“…Several studies described data fusion techniques combining chemical data of different analytical methods (Dearing, Thompson, Rechsteiner, & Marquardt, 2011;Mas, Tauler, & de Juan, 2011;Pere-Trepat & Tauler, 2006;Smilde, van der Werf, Bijlsma, van der Werff-van der Vat, & Jellema, 2005;Vera et al, 2011;Xu, Correa, & Goodacre, 2013). Most of them applied fused chromatographic techniques with a complementary analytical tool (Forshed, Idborg, & Jacobsson, 2007;Mas et al, 2011;Pere-Trepat & Tauler, 2006;Vera et al, 2011).…”
Section: Chemometric Analysis Of Combined Datamentioning
confidence: 99%
“…By using PLS regression models built from Raman spectra, Cooper et al demonstrated accurate predictions of chemical and physical properties, including the octane number and vapor pressures of petrochemical solutions [24]. This was further demonstrated by Dearing et al who predicted physical properties of crude oil distillates when combining IR, Raman, and nuclear magnetic resonance (NMR) information into data-fused models [25].…”
Section: Introductionmentioning
confidence: 97%
“…For example, the viscosity or American Petroleum Institute (API) gravity of crude oil has been successfully predicted using low‐field nuclear magnetic resonance (NMR) . Dearing et al combined Raman, infrared (IR), and NMR spectroscopic data to predict the API of crude oil products. De Peinder et al combined IR and NMR spectra to establish a correlation model between the composition and properties of the atmospheric residue using principal component analysis and partial least squares.…”
Section: Introductionmentioning
confidence: 99%